Challenges of Geotourism in South Africa: A Case Study of the Kruger National Park - Khodani Matshusa (MDPI AG, 2021)
As a new phenomenon, geotourism research is on the rise. Although South Africa has some interesting geoheritage sites, not much has been done to investigate the potential contribution of geotourism to the tourism sector, the protection of natural resources and employment generation, let alone the challenges that may be experienced in promoting geotourism. Therefore, this paper aims to describe the concept of geotourism and to identify the challenges of geotourism. It achieves this by looking at the case of the Kruger National Park, one of the largest game reserves in Africa, containing an abundance of geotourism sites. This research adopted a qualitative approach, with data collection involving semi-structured interviews with sixteen key informants to understand the challenges of geotourism. Manual content analysis was employed for analysing the data. A significant finding was that there were seven potential challenges in promoting and developing geotourism in the Kruger National Park: (1) a lack of packaging and marketing; (2) a lack of infrastructure; (3) security and access to geoheritage sites by tourists; (4) access to finance and markets; (5) destruction of geoheritage sites; (6) social challenges and (7) regulatory challenges. The results indicated that these challenges of geotourism can lead to negative perceptions about geotourism and can negatively impact the potential for geotourism development towards effective local social sustainability, especially for communities abutting the KNP. The major contribution of this study is its expansion of the geotourism academic literature through newly generated data on the challenges of geotourism in South Africa. Furthermore, this study theoretically contributes to the body of knowledge on geotourism and its challenges in Africa, particularly regarding the Kruger National Park.